احكام العدول عن الخطبة في الفقه و القضاء و القانون - كريم, فاروق عبدالله (Sulaimani Journal for Humanities, 2000)
The Judgement of law, court and the idea of experts of law concerning the breach of promise after agreement of engagement. Showing agreement concerning the marriage of a girl to a boy is not really regarded in itself as a contract because the girl and the boy can breach promise and the law has not put any punishment for this. But it happens that one of the sides breaches the promise while the other side has spent a lot of money for the preparation for family life for example the girl prepares the bride's outfit and sometimes she leaves her post or occupation either on her our wish or on the demand of the boy. Also it happens that the boy gives a lot of presents to the girl and sometime she gives her some money as a part of dowry in addition to the money the spends on the betrothal ceremonies and other cases of the same. How do law jurisprudence and court treat these cases? In addition to the monetary harm, there is no doubt, that the breach of promise from one side causes emotional harm and suffering to the other side especially if the side breaches promise is not satisfied only with this breach of promise but charges the other side with bad accusation; then what is the judgement of all these cases? Law is silent concerning most of the cases mentioned the cases the law speaks about are the following:- 1- Promise in engagement is not a contract. 2- When the boy gives any money or other things to the girl as a part of the dowry, the girl should return them not paying attention to which side breaches promise or whose fault it is. 3- The law of personal status asks the judge to use the civil law concerning the boy gives to the girl or the girl gives to the boy and the civil law in the article (612) allows the return of the presents if the giver asks for them and the present itself can be returned. These are all the cases that law speaks about and finds solution for except these, the law does not find solutions for any other cases, therefore the ideas of the experts in law are different and the courts gave different judgement for a long time in different countries and what the courts use now are:- 1. Promise in engagement is not a contract. 2. Breach of promise, in itself, does not have compensation. 3. If in the breach of promise anything happens that harms the other side, the court can give judgement to compensate the harm done to the other side on the basis of (negligence responsibility) but these judgements do not solve all the cases we spoke about and have some shortage. 4. Therefore, in this study, some ideas and points of view have been put forward and we returned to the root and bases of some of the legal and lawful general rules which give judgement and cause to form different ideas by the experts of law and in the courts also. The research consists of three parts:- First part: devoted to define (engagement) in law (jurisprudence) and court. 2.The result of the breach of promise. 3.The judgement of the harm which is caused as the result of the breach of promise. In the end we discussed the result we found out and showed our ideas and points of view about them.